International technology diffusion and the growth of TFP in the manufacturing sector of developing economies - Savvides, Andreas; Zachariadis, Marios (My University, 2005)
This paper evaluates various channels through which foreign technology diffuses to the manufacturing sector of developing economies. These economies undertake virtually no own R&D, so they rely on foreign technology to a much larger extent than developed economies. We investigate the direct effect of foreign R&D, as well as technology embodied in imports of intermediate and capital goods and foreign direct investment, on the growth of total factor productivity and value added in the manufacturing sector of 32 economies during 1965-92. We find that foreign R&D typically has the biggest positive impact on domestic productivity and value-added growth. Imports of capital goods and foreign direct investment also play a similar role, but their effect is of smaller magnitude and is not always significant.
Keywords: developing world; economic development; information technology; international trade; manufacturing